2015
DOI: 10.1039/c5ra04445f
|View full text |Cite
|
Sign up to set email alerts
|

Block copolymer as a novel functional phase in an aqueous biphasic system for species selective iodine extraction

Abstract: This article describes a newly designed block copolymer based aqueous biphasic system (ABS, composed of two immiscible aqueous phases) which is further utilized to study extraction behavior of three iodine species viz., I 2 , I À , and IO 4 À . Phase diagram and tie line data reveals the potential working range of this new biphasic system. Fluorescence, dynamic light scattering, transmission electron microscopy (TEM) and conductance data establish the micellar arrangement in solutions of this particular block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The analysis of the iodine molecule indicated that in the chosen ABS and in different temperatures almost all the iodine extracted to the top phase and an undetectable amount of iodine was in the bottom phase. Similar results have been obtained using ABS containing (PPG–PEG-PPG) copolymer and sodium tartrate in which 100% of elemental iodine extracted to top phase containing the copolymer . However, a comparison of this result with a previous one in which the partitioning behavior of iodine has been studied in ABS containing PEGDME 2000 and sodium nitrate, indicates that better partitioning of iodine is observed in ABS containing PEGDME 2000 and sodium nitrite.…”
Section: Results and Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The analysis of the iodine molecule indicated that in the chosen ABS and in different temperatures almost all the iodine extracted to the top phase and an undetectable amount of iodine was in the bottom phase. Similar results have been obtained using ABS containing (PPG–PEG-PPG) copolymer and sodium tartrate in which 100% of elemental iodine extracted to top phase containing the copolymer . However, a comparison of this result with a previous one in which the partitioning behavior of iodine has been studied in ABS containing PEGDME 2000 and sodium nitrate, indicates that better partitioning of iodine is observed in ABS containing PEGDME 2000 and sodium nitrite.…”
Section: Results and Discussionsupporting
confidence: 83%
“…Previously the partitioning of iodine has been investigated in aqueous two-phase systems containing PEGDME and sodium nitrate 5 and ABS containing poly-(propylene glycol) (PPG)-block-PEG-block-PPG (PPG−PEG-PPG) copolymer and sodium tartrate. 16 . Binodal curves were measured by the titration method using an apparatus described previously.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them are composed of poly­(ethylene glycol)- block -poly­(propylene glycol)- block -poly­(ethylene glycol) (PEG-PPG-PEG) vs various sulfate salts (Li 2 SO 4 , MgSO 4 , Na 2 SO 4 , and ZnSO 4 ) . Some others are also composed of poly­(propylene glycol)- block -poly­(ethylene glycol)- block -poly­(propylene glycol) (PPG-PEG-PPG) vs sodium tartrate, sodium acetate, or sodium citrate . Design of a new ABS demands its complete characterization in terms of phase diagrams which are conveniently achieved through a cloud point determination technique or turbidometric method or node determination method.…”
Section: Introductionmentioning
confidence: 99%